COMPARISON OF THE CALCULUS 1 PERFORMANCE OF ENGINEERING STUDENTS FROM STEM AND NON-STEM SHS STRANDS - Molina, Marivic G (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The study aimed to compare the Calculus 1 performance of engineering students from STEM and non-STEM SHS strands. A total of 486 engineering students comprise the respondents of the study. Of the 486 respondents, 466 students were from STEM SHS strand and 20 students were from non-STEM SHS strand. Data were collected using the (1) Midterm Departmental Exam (MDE), (2) Final Departmental Exam (FDE), and (3) Final Grade. The results revealed that engineering students performed poorly in Calculus 1. Moreover, a significant difference between the performance of engineering students from STEM and non-STEM SHS strands in finding derivatives was found. This showed that engineering students from STEM strand performed better in finding derivatives than the engineering students from the non-STEM strand. Similarly, a significant difference was found between the performance of engineering students from STEM and non-STEM strands in the applications of derivatives. This indicated that engineering students from STEM strand have a better performance in the applications of derivatives than the engineering students from the non-STEM strand. In regard to the Calculus 1 performance of engineering students from STEM and non-STEM strands, a significant difference was also found. The result revealed that engineering students from STEM strand outperformed the engineering students from the non-STEM strand in Calculus 1. The study recommended further investigation of the possible causes of students’ poor performance in Calculus 1 which include revisiting both the SHS and engineering curriculums.